Benefits of a Multi-institutional, Hybrid Approach to Teaching Course Design for Graduate Students, Postdoctoral Scholars, and Leaders - Hoffmann, Darren S.; Kearns, Katherine; Bovenmyer, Karen M.; Cumming, W. F. Preston; Drane, Leslie E.; Gonin, Madeleine; Kelly, Lisa; Rohde, Lisa; Tabassum, Shawana; Blay, Riley (Teaching and Learning Inquiry, 2021)
In this study, graduate students and postdoctoral scholars participated in a hybrid, multi-institutional workshop series about course design. Trainees developed college courses based on their research expertise, posting works-in-progress to a shared, online drive for peer review and collaboration. Learners also met weekly with local facilitators at their institution. The program led to similar learning outcomes as when the program was previously run in a face-to-face only format at one institution. However, the multi-institutional design led to additional benefits, especially for leaders at each institution, who described a rich learning community in their collaborative work.